CLIMATE IMPACTS ON WATER TABLE LEVELS BEHAVIOR IN A CONSERVATION AREA USING AN AUTOREGRESSIVE TIME SERIES MODEL - Manzione, R. L. (Revista Brasileira de Engenharia de Biossistemas, 2017)
Between 2013 and 2016, São Paulo State, Brazil, passed throw two marked periods of climatic anomalies, facing one of the worst droughts ever record and later the effects of El Ninõ South Oscilation (ENSO) phenomena, bringing direct impacts on water resources. The aim of this study was investigate the behaviour of water table depths from these climatological anomalies in the Ecological Station of Santa Barbara, municipality of Águas de Santa Barbara (SP), Brazil. From climate data and water table depths observed from September 2014 to August 2016, an autoregressive time series model (HARTT model) was tested to capture the response of groundwater levels due climatological inputs. We calculate response times from system inputs and trend of elevation in water levels along time. Climatological inputs influenced the behaviour of water table levels that presented a fast response, with marked influence of precipitation and trend of elevation during the monitoring period. This information is important for groundwater management, water dependable activities planning, land use parcelling and studies about the natural resources capacity of specific areas.